Modelo dialógico de prevenção e resolução de conflitos: é possível utilizá-lo como superação da violência causada em trotes universitários? - Vicente, Nathália Elisa Ferreira (Universidade Federal de São Carlos, 2021)
This theoretical essay aims to present the Dialogical Model of Conflict Prevention and Resolution (DPRM) as an alternative to overcome the violence that can occur in university pranks, considering the gender issue. To this end, first, general aspects of the problem of violence are presented, based on the WHO's position on the subject. Then, considering that we are socialized by violence, we bring dialogical possibilities of preventive socialization that combat violence committed against women. Finally, listing the principles of Dialogical Learning on which the MDPRC is based, we argue that it is possible to overcome conflictual relationships and prevent gender violence in university pranks with solidarity and love.
Dialogic model of conflict prevention and resolution: is it possible to use it to overcome violence caused by university pranks?
Keywords: Aprendizagem dialógica; Violência; Gênero; Universidades; Prevenção; Dialogical learning; Violence; Gender; Prevention; Universities; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO